Quality of care and challenges in medical convoy transfers during Hajj season 2023: a cross-sectional study - Alsaleh, Ghadah; Khan, Anas; Alabdulatif, Lamis; Alhazmi, Jumana; Althobaiti, Amira (Frontiers in Disaster and Emergency Medicine, 2025)
BackgroundThe Hajj pilgrimage, a significant spiritual journey for Muslims, occurs annually in Mecca, Saudi Arabia, attracting millions of participants from diverse backgrounds worldwide. This surge in pilgrims poses substantial challenges for healthcare services, as many face health risks due to physical exertion, dehydration, and exposure to infectious diseases. The unique healthcare demands during Hajj necessitate a thorough understanding of the quality of care provided and the challenges faced by medical convoys.ObjectivesThis study aims to assess the quality of care provided by medical convoys to medical conditions transferred to secondary or tertiary healthcare facilities during the Hajj season in 2023, while also examining the difficulties and challenges encountered by healthcare providers throughout the trip.Methods and materialsThis observational retrospective cross-sectional study involved 295 patients transferred from Makkah and Madinah hospitals to Arafat via a specialized medical convoy service during the 2023 Hajj season. Data were collected from electronic patient data sheets, documenting demographic characteristics, comorbidities, clinical diagnoses, transfer details, and the Risk Score for Transported Patients (RSTP). Ethical approval was obtained under IRB log Number: 23-452E from the Research Ethics Committee at King Fahad Medical City.ResultsAmong the 295 patients, the majority were males with an average age of 63.16 years. The most common nationalities were Asian (48.1%) and African (28.5%). Significant comorbidities included hypertension (34.2%) and diabetes mellitus (33.2%). RSTP indicated that 96.6% of patients had scores below 6. Nearly half were discharged within 72 h post-transfer, while a small percentage experienced deterioration or mortality. Most patients (58.3%) did not receive any medications or anesthesia, although 31.2% were administered analgesics. Common diagnoses included fractures (15.3%) and heat stroke (10.5%). Univariate logistic regression analysis revealed significant associations between higher RSTP and factors such as older age, presence of arrhythmias, need for respiratory support, lower Glasgow Coma Scale scores, total score, and blood pressure.ConclusionThis study highlights the diverse demographic characteristics and significant comorbidities of patients transferred during the Hajj season, indicating the need for tailored healthcare strategies that address the complexities of managing these patients. The strong association between higher RSTP scores and factors such as older age and arrhythmias underscores the importance of enhanced monitoring during transport. It is crucial to develop protocols that ensure patient safety and optimize outcomes in future healthcare delivery during Hajj.